Factors Influencing Student Learning Outcomes through Learning Motivation: A Case Study at A University in Vietnam - Tho, Huynh Thi Cam; Dinh, Nguyen Van; Vinh, Nguyen Tran Trong; Thuy, Le Thi Thanh; Phuong, Nguyen Thanh (Journal of Ecohumanism, 2024)
The study analyzes the factors affecting students' learning outcomes through learning motivation with a case study conducted at Nam Can Tho University. The research has developed a model incorporating six main factors: learning methods, family and friends, teaching methods, training program, facilities, and learning motivation. A mixed research approach was employed, integrating both qualitative and quantitative methods. A survey of 300 students was conducted to validate the hypotheses and research model. The structural equation model (SEM) analysis using SmartPls 4.0 indicated that the training program, family and friends, teaching methods, facilities, and learning methods positively influenced students' learning motivation. Among these, the training program had the most substantial impact, and learning motivation played a training program mediating role in improving students' learning outcomes. The findings are expected to enhance educational policies at Nam Can Tho University, aiming to foster student motivation and learning outcomes, thereby improving the quality of human resource training.